Los Angeles Dodgers 5 vs Atlanta Braves 2 at Dodger Stadium - Watkins, Howard::::::::: (1987)
Dodger #3 Steve Sax returns to dugout; Coach Tom Lasorda standing in dugout with arms folded; Viewed from centerfield